Radio adaptation of Kafka’s Metamorphosis as a “realistic work” in the context of selected film adaptations - Mikulášek, Alexej; Tkáč - Zabáková, Lenka (Slavia Centralis, 2021)
The study is based on previous research on the narrative strategies of Kafka’s prose Die Verwandlung (1915). It focuses on the radio play by director and screenwriter Josef Henke Proměna (1967) in comparison with film adaptations (Jan Němec, Valerij V. Fokin, Carlos Atanes). The playwright partially suppresses the latently present symbolic, surreal, parabolic, expressionist, existential, absurd aspects of Kafka’s two-dimensional text and presents it in an illusory realistic poetics. He excels in the art of "live dialogue", although at the same time he respects the peculiarities of the literary style. The radio play creates the illusion of a specific space and the "existence" of the presented scenes. Alienation plays a key role in many dimensions of this concept. The adaptation is not polemical, it depicts an unusually interesting character, similar to Kafka’s real destiny.